The Influence of Semantic Incongruency on Vocabulary Acquisition of Kurdish Learners of English Language - Diyar Lateef Omar (QALAAI ZANIST JOURNAL, 2023)
This study investigates the influence of semantic incongruency on the vocabulary acquisition of Kurdish learners of English and the different factors involved in resolving such incongruency. It also examines whether the level of language proficiency is key in facilitating learner understanding of this phenomenon. To these ends, a mixed method approach that features quantitative and qualitative data collection was adopted, for which two groups of learners were tested and interviewed. Findings indicate that semantic incongruency hinders vocabulary acquisition because it causes different types of lexical errors. Learners found semantically incongruent words that conceptually refer to two different domains easier to understand than those referring to one domain. Furthermore, knowledge of the collocational behavior of words and equivalent L3 words can help learners successfully use such vocabulary. The evidence derived in this study suggests that attention should be given to how meanings are ascribed to words in different languages and to the limitations presented by the tendency of learners to refer to their L1 as they use L2 vocabulary. Examining these issues is vital in increasing learner awareness of the differences between L1 and L2. Semantically congruent, collocation, and L3 words can be better incorporated into teaching and testing materials through inclusion in syllabi designed for vocabulary instruction.